2023
DOI: 10.3390/beverages9020045
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Fermented Beverages from Food Wastes/By-Products

Abstract: Current global research aims to explore the key role of diet and understand the benefits of a balanced diet. Furthermore, many authors have pointed to the added value of by-products as a solution to make food production chains more environmentally and economically sustainable. By-products emerge as an alternative matrix to fermentation, and the fermentation process has the potential to transform by-products into value-added products through an efficient and sustainable process. During fermentation, besides the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“… General diagram of the production process for plant-based fermented beverages. Common procedures were adapted from Alexandre et al [ 62 ] and Gil-Serna et al [ 63 ]. Created using (accessed on 11 December 2023).…”
Section: Figurementioning
confidence: 99%
“… General diagram of the production process for plant-based fermented beverages. Common procedures were adapted from Alexandre et al [ 62 ] and Gil-Serna et al [ 63 ]. Created using (accessed on 11 December 2023).…”
Section: Figurementioning
confidence: 99%
“…In the case of PBB production, this cannot always be applied [16]. Recent literature has also focused on the possibility of plant-based usage in the production of fermented beverages [17]. Fermentation is an old technology that has proven its benefits over time [18].…”
Section: Plant-based Beveragesmentioning
confidence: 99%
“…15 Probiotics such as Lactobacillus acidophilus and Lacticaseibacillus casei have been employed in the development of value-added dairy products such as cheese, yogurt, and whey-protein-based goods as a viable carrier of health-promoting nutrients including proteins, fats, and minerals. 15 Earlier studies have reported the extension of shelf life of cottage cheese by using natural antimicrobial compounds, plant derivatives, microbial flora, and its metabolites. 16,17,18 However, a meager amount of data is available on hand; therefore, the present research study was designed to evaluate the impact of free and encapsulated probiotics consisting of L. acidophilus and L. casei on the nutritional, physicochemical, and sensorial attributes of functional cottage cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Value-added products like cheese are preferred for their good profile of bioactive compounds such as phenolic substances and flavonoids that undergo metabolism by correlated actions of probiotics and enzymatic activities . Because of a wide array of nutritional significance, the product is well consumed worldwide including in South Asia, Indo-Pak, Egypt, and European countries . Probiotics such as Lactobacillus acidophilus and Lacticaseibacillus casei have been employed in the development of value-added dairy products such as cheese, yogurt, and whey-protein-based goods as a viable carrier of health-promoting nutrients including proteins, fats, and minerals .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation